2021
DOI: 10.2166/wst.2021.473
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of algae residue biochar and its application in methyl orange wastewater treatment

Abstract: In this work, Spirulina residue was used as the raw material to prepare different biochars by changing the pyrolysis time. Moreover, the obtained products were characterized by scanning electron microscopy, transmission electron microscopy, Raman spectroscopy, Fourier transform infrared spectroscopy, and X-ray diffraction energy spectra. This experiment used the batch adsorption method to study the adsorption effect of pH, dosage, and pyrolysis time on methyl orange. The adsorption of methyl orange onto Spirul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…This behavior was observed using mesoporous activated carbon [Azam et al, 2020] for the adsorption of MB and MO, it was found that the adsorption capacity decreases with the increase of Cads, causing an increase in the removal of dyes (98.5% for MO and 82% for MB). Moreover, the use of biochar from natural sources such as black sapote leaves [Herrera-González et al, 2019], E. crassipes [Nurhadi et al, 2019], Spirulina algae residues [Zhu et al, 2021], chestnut hull [Zhang et al, 2018] lychee seeds, banana peel [Srivatsav et al, 2020] obtaining in these works a removal percentage of 66.7 up to 99.9% for both dyes.…”
Section: Thermodynamic Analysis Of the Of Mb And Mo Adsorption Processmentioning
confidence: 99%
“…This behavior was observed using mesoporous activated carbon [Azam et al, 2020] for the adsorption of MB and MO, it was found that the adsorption capacity decreases with the increase of Cads, causing an increase in the removal of dyes (98.5% for MO and 82% for MB). Moreover, the use of biochar from natural sources such as black sapote leaves [Herrera-González et al, 2019], E. crassipes [Nurhadi et al, 2019], Spirulina algae residues [Zhu et al, 2021], chestnut hull [Zhang et al, 2018] lychee seeds, banana peel [Srivatsav et al, 2020] obtaining in these works a removal percentage of 66.7 up to 99.9% for both dyes.…”
Section: Thermodynamic Analysis Of the Of Mb And Mo Adsorption Processmentioning
confidence: 99%
“… 39 Calculated from the D peak and G peak integration of these three materials, the I D / I G value of MBC was much higher than that of MABC10% and MDBC10%, which may be that more minerals were introduced by ball milling to destroy the structure of C element. 42 The I D / I G ratios of MABC10% and MDBC10% were closer to 1 with few change, which may be due to that the addition of ATP and DE reduced the grain size of the C unit and promoted the amorphous structure and lattice defects of C. 37,43 …”
Section: Resultsmentioning
confidence: 89%
“…Both are plans of graphite, (002) and (100), respectively, and the former was traditionally used to estimate the degree of carbon graphitization. [35][36][37] For MABC10%, there were three characteristic peaks (2q = 30.6°, 40.8°and 50.7°) that correspond to attapulgite (JCPDS No. 21-0958) and MDBC10% showed peaks of amorphous opal-A at 2q = 21.6°.…”
Section: Sorbent Characterizationmentioning
confidence: 99%
“…Yi-di et al and Hao et al respectively studied the effect of pyrolysis temperature and pyrolysis time on the adsorption effect of seaweed adsorbents. It was found that increasing the temperature and shortening the time could reduce the graphite layer spacing and improve the stability of the biochar and adsorb more dye molecules [11,12].…”
Section: Preparation Of Adsorbents From Marine Debrismentioning
confidence: 99%